The Dated Alexander Staters of Tyre: A Die Study and Revised Chronology - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2025)
A die study of the dated Alexander gold staters of Tyre, struck between 332 and 305,1 reveals that the city employed 45 percent more dies than accounted for in Newell’s century old study of the dated coinage of Ake, since reattributed to Tyre. It identifies several additions and corrections to Price’s classification of the dated gold staters. Remarkably, fifty-five percent of Tyre’s total gold emission was produced over seven years, during Alexander the Great’s lifetime. Its value was twice that of the contemporary silver output. Comparing the number of stater obverse dies used each year at Tyre with those from Sidon, the study establishes that Tyre’s calendar was based on a Spring calendar year, while the start of the regnal era of a king was defined under an accession year dating system. With this new understanding, it is clear that the dating era of the Alexandrine issues began in the Spring of 348, sixteen years prior to the fall of Tyre to the Macedonians. Between 329 and 310 each of the local calendar years of Tyre and Sidon overlapped for only six months, rather than being congruent. In 310 the Greek/Macedonian calendar displaced the Tyrian calendar with dates defined on the era of Antigonus. A revised chronological calibration and the annual sequence of die usage for the dated Alexander issues of both Tyre and Sidon is presented. The revised chronology of the dated Alexanders of Tyre conforms precisely to all the constraining evidence and data points that arise from the reattribution to Tyre of the dated issues previously attributed to Ake. This is a further substantiation of the reattribution. It closely aligns the iconographic and epigraphic progression evident in the coinage with parallel developments at Sidon. It brings the peak of the dated gold emission at each city during Alexander’s lifetime into chronological alignment.